Effect of Different Cascara Tea Formulas on the Addition of Dayak Onion and Stevia - Harahap, Risda Munarti Rusdy; Kasim, Anwar; Kasim, Fitriani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Formulation in making tea is necessary to produce quality products with a distinctive taste and optimal health benefits. Cascara is a dried tea product produced from coffee skin waste. It has been reported to have potential as a natural antioxidant because it contains secondary metabolite compounds such as polyphenols. Dayak onion bulbs are reported to contain flavonoids that are useful for preventing and alleviating complaints due to degenerative diseases such as hypertension and controlling blood sugar levels. Stevia is a plant known as sugar leaves or non-calorie natural sweeteners whose dried leaves have 30 times the sweetness of sucrose. The purpose of this study was to combine coffee fruit skin (cascara), Dayak onion, and stevia in herbal tea formulations to explore health potential and see the effect of differences in cascara, dayak onion, and stevia tea formulations on pH values, moisture content, and ash content according to the Indonesian National Standard (SNI). This study used a Factorial Completely Randomized Design (CRD). The results of this study indicate that the moisture content of herbal tea bags ranges from 9.05%-11.48%, with certain formulations (C, D, E, and F) meeting SNI standards. The ash content of herbal tea bags ranges from 3.58%-7.35%, reflecting the mineral content, with higher stevia concentrations correlating with increased ash content. The pH value of the brewed herbal tea ranges from 4.34-5.12, indicating that higher concentrations of Dayak onion produce higher pH values while increasing stevia concentrations lower pH. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land